2005
DOI: 10.1136/bjo.2004.046755
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma endothelin-1 levels in patients with progressive open angle glaucoma

Abstract: Aim: To compare the plasma levels of endothelin-1 (ET-1) between patients with primary open angle glaucoma with visual field progression despite normal or normalised intraocular pressure and patients with stabile visual fields in a retrospective study. Methods: The progressive group consisted of 16 primary open angle glaucoma patients and the group with stable visual field consisted of 15 patients. After a 30 minute rest in a supine position, venous blood was obtained for ET-1 dosing. Difference in the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 33 publications
3
82
0
5
Order By: Relevance
“…A number of previous cross-sectional studies have shown that basal levels of plasma (or serum) ET-1 in patients with glaucoma were elevated at a higher level than control subjects. [12][13][14] Conversely, other studies showed no significant difference in plasma (or serum) ET-1 between subjects with glaucoma patients and normal control subjects [54][55][56][57] or lower levels of plasma ET-1 in patients with glaucoma when compared with normal subjects. 15 Although the conflicting conclusions indicate that no consensus regarding plasma (or serum) levels of ET-1 in patients with glaucoma have been reached, it is possible that data from all studies are accurate, since plasma (or serum) ET-1 levels may fluctuate due to seasonal, circadian, and other factors.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A number of previous cross-sectional studies have shown that basal levels of plasma (or serum) ET-1 in patients with glaucoma were elevated at a higher level than control subjects. [12][13][14] Conversely, other studies showed no significant difference in plasma (or serum) ET-1 between subjects with glaucoma patients and normal control subjects [54][55][56][57] or lower levels of plasma ET-1 in patients with glaucoma when compared with normal subjects. 15 Although the conflicting conclusions indicate that no consensus regarding plasma (or serum) levels of ET-1 in patients with glaucoma have been reached, it is possible that data from all studies are accurate, since plasma (or serum) ET-1 levels may fluctuate due to seasonal, circadian, and other factors.…”
Section: Discussionmentioning
confidence: 83%
“…3,4 This is because, in addition to the elevated IOPs, ocular blood circulation, oxidative stress, and other mechanisms are also believed to be involved in the GON etiology. Regarding ocular blood circulation, evidence from numerous reports indicating that insufficient retinal and optic disc blood supply are involved in the GON etiology includes the following: (1) Disc hemorrhages frequently exist in patients with open-angle glaucoma (OAG) [6][7][8] ; (2) retinal vascular diseases, such as retinal vein occlusion, are frequently associated with OAG patients with OAG 10,11 ; (4) there are abnormal levels of the concentration of plasma endothelin-1 (ET-1) in patients with OAG as compared with healthy control subjects [12][13][14][15] ; (5) platelet aggregation ability is remarkably increased in patients with OAG compared with that in normal subjects. 16 As for oxidative stress, reactive oxygen species (ROS) are produced as a consequence of normal aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible theory for the underlying cause of the increased RVP is the production of vasoactive molecules such as endothelin-1 (ET-1) produced either locally by the endothelial cells or by the surrounding tissue or produced by diffusion throughout the circulating blood to smooth muscle cells or pericytes [28]. In people with atherosclerotic risk factors and well in those with the Flammer syndrome, the arteries produce an increased amount of ET-1 increasing both the concentration of ET-1 in the circulating blood as well in the surrounding tissue of the artery [34][35][36]. Hypoxic tissues may also increase ET-1 levels in the circulating blood and thus induce a secondary vascular dysregulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…The ET-1-dependent vascular dysregulation known as Flammer syndrome [18] may be one of the important causes of NTG. Moreover, Emre et al reported that glaucoma patients (with either normal IOP or normalized IOP after treatment) showing visual field progression had increased plasma ET-1 levels [19] . However, Chen et al found no correlation between plasma levels of ET-1 and the severity of glaucoma [20] .…”
Section: Et-1 and Normal-tension Glaucoma (Ntg)mentioning
confidence: 99%